ANALISIS CORPORATE SOCIAL RESPONSIBILITY, LOYALITAS NASABAH, CORPORATE IMAGE DAN KEPUASAN NASABAH PADA PERBANKAN SYARIAH - Fetria Eka Yudiana; Joko Setyono (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
The purpose of this research is to analize the effect of the implementation of Corporate Social Responsibility (CSR) on customer loyalty to the corporate image and customer satisfaction as an intervening variable. This research is a survey research which used a quantitative approach. The data were obtained from 100 respondents from all customers Sariah Banking in Central Java and Yogyakarta by using purposive sampling technique. The research model testing technique used the path analysis approach using multiple regression. The results of this research suggests that CSR is positive and significant impact on the corporate image, CSR positive and significant impact on customer satisfaction, corporate image positive and significant impact on customer loyalty, customer satisfaction positive and significant impact on customer loyalty, CSR has positive effect but not significant on customer loyalty.